WORKING HOURS COMPENSATION AGREEMENT AND THE 2017 LABOR REFORM (CIPEEX, 2025)
The present study aims to analyze the regulation of working hours and the hours bank considering the consolidation of labor laws, especially after the 2017 labor reform. Through bibliographical and qualitative analysis, the research aims to investigate the legal limits, the forms of compensation for hours and the impacts of flexibilization for employers and employees. It has been demonstrated that the working hours compensation agreement emerged as an alternative to the rigidity of traditional working hours, allowing adaptation to the employer's needs without the payment of immediate overtime. Working hours compensation requires clear agreements to avoid overload and disputes. It is concluded that, according to data from the superior labor court in 2023, there was a significant increase in labor lawsuits related to the misuse of the hours bank. And, further, working hours management must respect the principles of human dignity and value of workers' time, balancing productivity and fundamental rights.